Agricultural traits and popping expansion of the popcorn hybrid IAC 125 under different plant densities and irrigation water depth levels (Acta Scientiarum. Agronomy, 2023)
Popcorn (Zea mays L. everta) is a specialty crop with a higher aggregate economic value than that of common maize. In Brazil, national literature is still incipient and contradictory in terms of plant population management and water requirements. Furthermore, the interaction between these factors has not been reported, despite the increasing cultivation of popcorn. The objective of this trial was to determine whether agricultural traits and popping expansion from hybrid IAC 125 could be affected by plant density and levels of irrigation water, in addition to determining the significance level of the interaction between both factors. We investigated five plant populations (40,000, 55,000, 70,000, 85,000, and 100,000 plants ha-1) and five different levels of water depth in 2014/2015 [574.86 (without supplementary irrigation), 609.86, 644.86, 679.86 (control), and 714.86 mm] and 2015/2016 [857.4 (without supplementary irrigation), 867.26, 886.60, 916.78 (control), and 959.81 mm] using a complete block design with split-plot, comprising a main plot (for plant populations) and subplot (for water depth), with six replicates for each set. We found increasing linear effects from grain yield under population density and levels of water depth, but this interaction was not significant. Moreover, the popping expansion for the main effects and the interaction between plant populations and water depth, were not significant.